2017
DOI: 10.1590/s1984-29612017019
|View full text |Cite
|
Sign up to set email alerts
|

First outbreak and subsequent cases of Trypanosoma vivax in the state of Goiás, Brazil

Abstract: Trypanosomiasis caused by Trypanosoma vivax has increased the reports in Brazil in the last decade. An outbreak is herein first reported in the state of Goiás, from May 2016 to January 2017. The outbreak start occurred in the city of Ipameri (Goiás) after the introduction of 18 auctioned cows from the state of Minas Gerais. Direct parasitological test (blood smears) and polymerase chain reactions targeting the catL genes diagnosed T. vivax infection. Fifty six cows from a herd of 161 were infected; 12 died dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 11 publications
3
23
0
8
Order By: Relevance
“…Over the past 16 years, T. vivax has spread rapidly across Brazil (Linhares et al ., 2006; Batista et al ., 2007; Carvalho et al ., 2008; Guerra et al ., 2008; Silva et al ., 2009; Cadioli et al ., 2012; Pimentel et al ., 2012; Andrade Neto e André, 2015; Costa et al ., 2016; Bastos et al ., 2017; Vieira et al ., 2017; Lopes et al ., 2018). In 11 of the publications cited, outbreaks occurred in Girolando dairy cattle; 10 reported the introduction of new animals to the herd and seven reported the use of oxytocin and/or vaccines as the predisposing factor for the occurrence of trypanosomosis in the respective herds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 16 years, T. vivax has spread rapidly across Brazil (Linhares et al ., 2006; Batista et al ., 2007; Carvalho et al ., 2008; Guerra et al ., 2008; Silva et al ., 2009; Cadioli et al ., 2012; Pimentel et al ., 2012; Andrade Neto e André, 2015; Costa et al ., 2016; Bastos et al ., 2017; Vieira et al ., 2017; Lopes et al ., 2018). In 11 of the publications cited, outbreaks occurred in Girolando dairy cattle; 10 reported the introduction of new animals to the herd and seven reported the use of oxytocin and/or vaccines as the predisposing factor for the occurrence of trypanosomosis in the respective herds.…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa, the transmission of this protozoa occurs biologically through the tsetse fly ( Glossina spp.). In Central and South America, transmission occurs mechanically by biting flies (tabanids, Stomoxys calcitrans and Haematobia irritans) or by iatrogenic means (Cadioli et al ., 2012; Dagnachew and Bezie, 2015; Bastos et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the expanding geographic distribution of T. vivax has resulted from the livestock moving between endemic regions and those where the conditions are favorable (climate favorable to hematophagous dipterans, animals lacking prior immunity to the parasite, and the permanent practice of sharing blood-contaminated needles [fomites] during vaccination and application of oxytocin) (Cadioli et al, 2012;Bastos et al, 2017;Andrade Neto et al, 2019). The results showed that cows are significantly more exposed to T. vivax compared to calves, which may be related to the longer period in contact with hematophagous mechanical vectors and fomites (especially due to shared needles).…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not find significant differences regarding the presence of antibodies against T. vivax across the cows sampled in the four states, which suggests that the parasite is being scattered across the country. Such expansion of its geographical distribution in Brazil is mainly due to the movement of cattle from endemic regions to those where there is a favorable epidemiological situation (climatic conditions favoring the presence of hematophagous dipterans, animals without prior immunity to the parasite in question and long-standing practice of sharing needles contaminated with blood [fomites] during vaccination and application of oxytocin) (CADIOLI et al, 2012;BASTOS et al, 2017).…”
Section: Discussionmentioning
confidence: 99%